Education on Assistance for Drug-Resistant TB Patients Since Diagnosis to Community TB Cadres Through Cadre Training Activities in Kediri City in 2025 - Nurita Nilasari Bunga Kharisma Arifiana Putri; Heny Kristanto; Yunarsih; Sucipto; Puguh Santoso; Betristasia Puspitasari (Journal of Community Service for Health, 2025)
Drug-resistant tuberculosis (DR-TB) or drug resistance is a condition where TB germs can no longer be killed with first-line anti-tuberculosis drugs (OAT), so they must be treated with second-line OAT (Drug-resistant TB Patient Pocket Book, 2020). Drug-resistant tuberculosis (DR-TB) is still a threat in TB control and is one of the main public health problems in many countries in the world. The data collection technique in this activity was through a questionnaire survey given before and after the presentation of the material on Assisting Drug-resistant TB Patients. The sample was 46 participants who were TB Cadres from each Sub-district throughout Kediri City. The data analysis used in this activity by measuring the correct and incorrect answers between the pre- and posttests that had been filled out by the training participants. The results of the questionnaire filled out by the activity participants showed an increase in knowledge about Assisting Drug-resistant TB Patients Since being diagnosed. The success of drug-resistant TB treatment is also inseparable from the important role of the family, health workers, and patient companions who always support patients to undergo DR-TB treatment until completion. Effective assistance will affect the success of treatment, the patient's quality of life, and reduce the risk of transmission of drug-resistant TB in the community.